Novel Role for miR-1290 in Host Species Specificity of Influenza A Virus - Sheng-Yu Huang; Chih-Heng Huang; Chi-Jene Chen; Ting-Wen Chen; Chun-Yuan Lin; Yueh-Te Lin; Shu-Ming Kuo; Chung-Guei Huang; Li-Ang Lee; Yi-Hsiang Chen; Mei-Feng Chen; Rei-Lin Kuo; et al. (Elsevier, 2019)
The role of microRNA (miRNA) in influenza A virus (IAV) host species specificity is not well understood as yet. Here, we show that a host miRNA, miR-1290, is induced through the extracellular signal-regulated kinase (ERK) pathway upon IAV infection and is associated with increased viral titers in human cells and ferret animal models. miR-1290 was observed to target and reduce expression of the host vimentin gene. Vimentin binds with the PB2 subunit of influenza A virus ribonucleoprotein (vRNP), and knockdown of vimentin expression significantly increased vRNP nuclear retention and viral polymerase activity. Interestingly, miR-1290 was not detected in either chicken cells or mouse animal models, and the 3' UTR of the chicken vimentin gene contains no binding site for miR-1290. These findings point to a host species-specific mechanism by which IAV upregulates miR-1290 to disrupt vimentin expression and retain vRNP in the nucleus, thereby enhancing viral polymerase activity and viral replication. Keywords: influenza A virus, miR-1290, vimentin, viral ribonucleoprotein, vRNP, miRNA, virus, host species-specificity, ferret